Oralità, imitazione e apprendimento dell’italiano L2: il caso degli immigrati senegalesi scarsamente scolarizzati - De Meo, Anna (Incontri. Rivista europea di studi italiani, 2018)
Orality, imitation and L2 Italian learning The case of Senegalese immigrants with little or no education In this study, the focus is on a particular group of adult learners, namely Senagalese immigrants with an exclusively oral mother tongue (Wolof), a low level of schooling in a second language (French and/or Arabic), two possible school paths (French school or Koranic school) and an elementary level of oral competence of the Italian language. The research data present two different ways of managing the intonational parameters of Italian L2 which can be traced back to the different educational models to which they were exposed in their home country. Spectroacoustic analysis of an oral L2 Italian corpus, obtained through an imitation task, demonstrates a more efficient ability in managing intonation in short statements in L2 utterances of the Koranic school learners. This led to rethinking the teaching intervention in the classroom, adapting the approach to the skills developed in the limited educational path at home, with a re-evaluation of imitation and fixation activities comparable to pattern drills. The final result can be identified in the positive impact on the motivational levels in learning a second language with similar positive effects on reading and writing skills.